Detection Bacteria of Escherichia coli in Broiller Chicken in Tradisional Market Mataram City - Dita Febrianti; Alfiana Laili Dwi Agustin; Novarina Sulsia Ista'In Ningtyas (Mandalika Veterinary Journal, 2022)
Escherichia coli bacteria are bacteria that are susceptible to contaminating chicken meat. Bacterial contamination in chicken meat generally comes from the room, equipment or table where the chicken is abattoir, as well as the water used during the slaughtering process to the processing of chicken meat. The impact if people consume chicken meat contaminated with  Escherichia coli bacteria with general symptoms of abdominal pain, diarrhea, vomiting, fever and typhus. This study aims that determine the presence or absence of Esherichia coli bacteria in chicken meat sold in the traditional market of Mataram City. The samples of this research taken by purposive  sampling. The method of this research using detect disease to estimate proportion, where 10 samples of broiler chicken meat were taken from 19 traders in the Mataram City Traditional Market and analyzed descriptively. From 10 samples of broiler chicken tested, 4 of them were contaminated with Escherichia coli bacteria. The results showed that 40% of broiler chicken meat in the Mataram City Traditional Market were contaminated with Esherichia coli bacteria.